Operations management : a supply chain approach - Waller, Derek L. (International Thomson Business, 1999)
Positioning operations management. Strategy of organizations. Site selection. Quality management. An environmental balance. Design of the product. Process design and the operations network. Human resources in the system design. Forecasting customer demand. Design of the facility layout...